Efecto del tiempo y temperatura de secado sobre la humedad final y variación del porcentaje de FOS (FRUCTO-OLIGOSACÁRIDOS) en rodajas de Yacón (Smallanthus sonchifolius) - Cordova Coronado, Miguel Ángel (2013)
In the present study aimed to examine the effect of temperature and drying time on moisture and loss of fructo-oligosaccharides (FOS) from yacon slices (Smallanthus sonchifolius). For less humidity and less loss of oligofructosaccharides sliced yacon (Smallanthus sonchifolius). To meet this objective, we used the central composite rotational design (DCCR) which pointed drawn 11 experimental trials to evaluate the temperature and drying time. Was used for drying yacón with 94.68% moisture. Said yacón was conditioned so that was obtained sliced and then subjected to a drying process at different temperatures and times. Later determined moisture loss and variation of FOS. It was concluded that higher drying times lower the moisture content and the lower the drying temperature the lower the variation of FOS. Determined not to significantly affect the time and the drying temperature on the moisture loss. Moreover, time and temperature, both in linear and quadratic variation significantly affect FOS. Also optimized the drying time and temperature for less variation of sliced yacon FOS (Smallanthus Sonchifolius), which were: 3-4 h and 75-95 ° C.